Don't forget the girl : a novel - McKanna, Rebecca (Sourcebooks Landmark, 2023)
"We never remember the dead girls. We never forget the killers. Twelve years ago, 18-year-old University of Iowa freshman Abby Hartmann disappeared. Now, Jon Allan Blue, the serial killer suspected of her murder, is about to be executed. Abby's best friends, Bree and Chelsea, watch as Abby's memory is unearthed and overshadowed by Blue and his flashier crimes. The friends, estranged in the wake of Abby's disappearance, and suffering from years of unvoiced resentments, must reunite when a high-profile podcast dedicates its next season to Blue's murders. Tense and introspective, Don't Forget the Girl is an astonishing debut thriller that mines the complexities of friendship and the secrets between us that we may take to the grave"--